Emotion analysis of reaction to Terrorism on Twitter - Harb, Jonathas G. D.; Becker, Karin (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2018: Anais do XXXIII Simpósio Brasileiro de Banco de Dados, 2018)
Terrorism events impact people in several manners. Reactions may include losing sense of safety and experiencing angry and fear, among others. The social media has become an important mean where people express themselves. We target Twitter to investigate the emotional reaction people have to terrorism events. For this purpose, we analyze emotions in tweets along with demographic data. Tracking emotional reaction can help in defining specific assistance programs. In our approach we collect a corpus of tweets related to two terrorism events, classify emotions, extract user location and estimate user age and gender with use of available tools. Results showed an emotion shift due to the events and a difference on the reaction from one event to another.